2010
DOI: 10.1099/vir.0.017814-0
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for a common nomenclature for viral clades that form the species varicella-zoster virus: summary of VZV Nomenclature Meeting 2008, Barts and the London School of Medicine and Dentistry, 24-25 July 2008

Abstract: Varicella-zoster virus (VZV), the cause of chickenpox and zoster, was the first human herpesvirus to be sequenced fully and the first for which vaccines have been licensed and widely used. Three groups have published genotyping schemes based on single nucleotide polymorphisms (SNPs) and, between them, have identified five distinct phylogenetic clades, with an additional two putative clades. Sequencing of over 23 whole VZV genomes from around the world further refined the phylogenetic distinctions between SNP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 43 publications
2
113
0
1
Order By: Relevance
“…Viral genomic studies have identified five viral clades and their geographical distribution: clades 1, 3 and 5 are of European origin; clade 2 includes Asian strains such as the parental Oka strain, from which varicella and zoster vaccines were derived; and clade 4 contains African strains 8 . Varicella epidemiology and disease burden have been studied primarily in developed countries.…”
Section: Epidemiology Varicellamentioning
confidence: 99%
“…Viral genomic studies have identified five viral clades and their geographical distribution: clades 1, 3 and 5 are of European origin; clade 2 includes Asian strains such as the parental Oka strain, from which varicella and zoster vaccines were derived; and clade 4 contains African strains 8 . Varicella epidemiology and disease burden have been studied primarily in developed countries.…”
Section: Epidemiology Varicellamentioning
confidence: 99%
“…VZV nomenclature currently recognizes nine clades, six established clades designated by Arabic numerals 1 to 6, and three provisional clades designated by the Roman numerals VII, VIII and IX [3,4]. In accordance with the nomenclature system proposed in 2008, two WGSs are needed to redesignate a provisional clade as established.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the availability of high-throughput NGS, genotyping strategies relied on targeted sequencing of informative SNPs. Several groups published methods for identifying VZV clades using targeted SNP analysis that were useful for discriminating the seven clades recognized at that time [3,6]. Those methods are now unsuitable for the reliable discrimination of the currently recognized VZV clades.…”
Section: Introductionmentioning
confidence: 99%
“…While clades 1, 3, and 5 are common in Europe, clade 2 is most widely distributed in Japan and East Asia. [4][5][6] To prevent varicella, the Oka strain varicella vaccine was developed in Japan in 1974, and the MAV strain varicella vaccine was developed in Korea in 1993. Both vaccines contain live attenuated viruses that cluster in clade 2.…”
Section: Introductionmentioning
confidence: 99%
“…Varicella usually affects children aged 2-8 y. [1][2][3] Based on the universal nomenclature for VZV, VZV is categorized into 5 clades (clades [1][2][3][4][5]. While clades 1, 3, and 5 are common in Europe, clade 2 is most widely distributed in Japan and East Asia.…”
Section: Introductionmentioning
confidence: 99%